Comparison of goalscoring patterns between the 2018 and 2022 FIFA World Cups - Degrenne, Olivier; Carling, Christopher (Frontiers in Sports and Active Living, 2024)
The main aim of this study was to compare goal scoring patterns between the two most recent FIFA World CupTM (WC) tournaments: Russia 2018 and Qatar 2022. Match performance data were extracted using the ProVision database (StatsPerform, Chicago, USA). Variables used to analyse goals (not including penalty shootout goals) included the match period in which these were scored, the type of action and different types of play, body part used, defensive pressure, possession duration and expected goals (xG) values. A Chi-square test was used to compare qualitative variables across competitions while quantitative variables were compared using a nonparametric Mann–Whitney U-test for independent samples. Altogether, 169 goals were scored in WC 2018 vs. 172 goals in WC 2022. No differences occurred across competitions for the period in which goals were scored. In both tournaments the majority was scored in the second-half and towards the end of play. Significant differences were observed for the type of action, type of play and body part used prior to scoring a goal (p < .05). These differences can be explained by the record number of own goals and goals scored from set-pieces in 2018 and an increase in goals scored from open-play (from positional attacks notably) in 2022. Analysis of open-play situations showed that teams recorded a higher xG value and converted more of their chances (xG = 122.8 vs. 128 goals, xG difference = +5.2) in 2022 thus were more efficient compared with 2018. In sum, goal scoring patterns largely differed between the two most recent World Cup tournaments.